2023
DOI: 10.1371/journal.pbio.3001979
|View full text |Cite
|
Sign up to set email alerts
|

Why have we not yet solved the challenge of plastic degradation by biological means?

Abstract: The invention of fossil fuel–derived plastics changed and reshaped society for the better; however, their mass production has created an unprecedented accumulation of waste and an environmental crisis. Scientists are searching for better ways to reduce plastic waste than the current methods of mechanical recycling and incineration, which are only partial solutions. Biological means of breaking down plastics have been investigated as alternatives, with studies mostly focusing on using microorganisms to biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Fragmentation will increase the surface area at which chemical and microbiological degradation can occur. Several studies have also shown that microbiota and enzymes associated with the digestive tract of invertebrates may accelerate the breakdown of plastics (Ali et al, 2021; Bertocchini & Arias, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Fragmentation will increase the surface area at which chemical and microbiological degradation can occur. Several studies have also shown that microbiota and enzymes associated with the digestive tract of invertebrates may accelerate the breakdown of plastics (Ali et al, 2021; Bertocchini & Arias, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…[149,150] The first three methods are associated with several drawbacks such as high cost, energy inputs, and production of unwanted toxic by-products (carbon and nitrogen oxides) thus making biodegradation a highly reliable method for decomposing plastic particles. [151] The biodegradation of plastic by microbes has received much attention in recent years due to its accessibility, easy modulation capabilities, and lower toxic effects on the environment. Several microorganisms such as Pseudomonas sp., Fusarium solani, Aspergillus nidulans, and Aureobasidium pullulans are known for their plastic degrading capabilities from terrestrial and marine environments under aerobic as well as anaerobic conditions.…”
Section: Bioremediation Of Pnps: Plastic Degrading Proteins and Their...mentioning
confidence: 99%
“…The latter part of the Anthropocene can now be referred to as the Plasticene (1), with plastic debris providing a new ecological niche known as the plastisphere (2). Plastics degrade into microplastics (MPs), with MP contamination of our environment recognized with mounting concerns (3,4), especially as chemical breakdown is very slow and biodegradation pathways are limited (5). Human MP exposure arises from both from use of items manufactured from plastic, and as a result of poor disposal of plastic waste that results in plastic pollution (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%